Rencana Strategis Bisnis Jualan Online di Masa Pandemi Covid-19: Online Selling Business Strategic Plan in the Covid-19 Pandemic Period - Budi Harto; Kasmanto Rinaldi; Ariraya Sulistya (Engineering and Technology International Journal, 2021)
Online business is currently growing rapidly. This is because shopping online makes the limitations of distance, time, and cost easily overcome. There are many factors that influence someone to shop online, ranging from lower costs, quality of goods, trust, consumer perceptions of risk, to other factors. The purpose of this study was to analyze the effect of risk perception, consumer involvement and consumer trust on consumer buying interest online.